2017
DOI: 10.1272/jnms.84.291
|View full text |Cite
|
Sign up to set email alerts
|

A Drug Interaction between Crizotinib and Warfarin in Non-Small-Cell Lung Cancer: A Case Report

Abstract: We report a case of increased prothrombin time-international normalized ratio (PT-INR) when crizotinib and warfarin were co-administered. A 74-year-old Japanese woman presented to the hospital with dyspnea, and was diagnosed with anaplastic lymphoma kinase (ALK)-positive non-small-cell lung cancer (NSCLC). Three years after surgical resection of the tumor, the patient started crizotinib because of the recurrence of NSCLC. She received 2 mg/day warfarin due to a medical history of cerebral infarction and chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…13,69 Coadministration of crizotinib increases the AUC and C max values for midazolam (a sensitive CYP3A substrate), by 116% and 32%, 265% and 102%, and 250% and 139%, on average, at crizotinib dose levels of 100 mg daily, 250 mg twice daily, and 300 mg twice daily, respectively, suggesting that crizotinib is a moderate CYP3A inhibitor. 29,69 The warfarin (R) enantiomer is metabolized by CYP3A4, kubomura et al 70 reported a case of increased prothrombin time-international normalized ratio when crizotinib and warfarin were coadministered. Therefore, the concomitant use of crizotinib with sensitive CYP3A substrates should be avoided, if the concomitant use of crizotinib is unavoidable, reducing the dose of CYP3A substrates is recommended.…”
Section: Crizotinibmentioning
confidence: 99%
“…13,69 Coadministration of crizotinib increases the AUC and C max values for midazolam (a sensitive CYP3A substrate), by 116% and 32%, 265% and 102%, and 250% and 139%, on average, at crizotinib dose levels of 100 mg daily, 250 mg twice daily, and 300 mg twice daily, respectively, suggesting that crizotinib is a moderate CYP3A inhibitor. 29,69 The warfarin (R) enantiomer is metabolized by CYP3A4, kubomura et al 70 reported a case of increased prothrombin time-international normalized ratio when crizotinib and warfarin were coadministered. Therefore, the concomitant use of crizotinib with sensitive CYP3A substrates should be avoided, if the concomitant use of crizotinib is unavoidable, reducing the dose of CYP3A substrates is recommended.…”
Section: Crizotinibmentioning
confidence: 99%
“…Statements on drug interactions between warfarin and alectinib or crizotinib are not available in the prescription information for these drugs. Although some studies have reported on the drug interactions between warfarin and each of the above-mentioned ALK-TKIs [ 5 7 ], INR elevation during treatment with alectinib, crizotinib, or ceritinib concurrent use of warfarin and bucolome has not been reported. Here, we report the first case of a patient receiving warfarin and bucolome whose INR increased after sequential treatment with alectinib, crizotinib, and ceritinib.…”
Section: Introductionmentioning
confidence: 99%